Ultrasound-Guided Collagen Peptides Injections Combined with Focused Extracorporeal Shockwave Therapy and Therapeutic Exercise in Chronic Partial Common Extensor Tendon Tears at Elbow Lateral Epicondyle: A Retrospective Case Series - Nicolò Vitale; Luca Latini; Marco Di Gesù; Ilias Vurliotis; Marianna Capecci; Valerio Sebastiano Amico; Florentin Ananu Vreju; Emilio Filippucci (Life, 2026)
Background: Lateral elbow tendinopathy (LET) is a common upper-limb musculoskeletal disorder causing pain during gripping activities, reduced work capacity, and functional limitation. LET is currently considered a predominantly degenerative condition characterized by collagen disorganization, extracellular matrix changes, neovascularization, and impaired tendon healing. Objective: To evaluate short-term clinical and functional outcomes of a multimodal protocol including focused extracorporeal shock wave therapy (f-ESWT), ultrasound-guided intralesional injection of low-molecular-weight peptides (LWPs) derived from hydrolyzed bovine collagen and therapeutic exercise in patients with chronic LET unresponsive to standardized conservative therapy. Methods: This retrospective observational study included 11 screened patients; 10 completed follow-up. Eligibility required age ≥ 18 years, symptoms ≥ 3 months, positive provocation tests, ultrasound-confirmed common extensor tendon pathology, and incomplete response to prior treatment. All patients received f-ESWT before ultrasound-guided LWPs injection and performed progressive loading exercises. Outcomes included Patient-Rated Tennis Elbow Evaluation (PRTEE), grip strength, and clinical provocation tests at baseline (T0; Day 0) and at T1 (Day 51, 30 days after injection). Results: PRTEE pain improved by 31.2 points (95% CI 22.2–40.2; Cohen’s d_z = 2.48) and PRTEE function by 32.6 points (95% CI 26.7–38.5; d_z = 3.95). Mean maximal strength and maximal strength improved by 4.61 kg (95% CI 2.89–6.32) and 4.02 kg (95% CI 2.36–5.68), respectively. Clinical test severity decreased by an estimated 2.5 points (95% CI 2.0–3.0). No adverse events were reported. Conclusions: Patients showed clinically meaningful short-term improvements in pain, function, and strength following the sequential multimodal management strategy. However, the retrospective design, small sample, lack of control group, and short follow-up preclude causal attribution and require confirmation in prospective controlled studies.